The political discourses of heritage. A case of asset activation in Argentina - Mariano, Mercedes (2021)
Introduction This work is part of an interdisciplinary program of heritage studies, specifically in a research Project that seeks to analyze the relationship that local communities in intermediate cities establish with cultural heritage. In this sense, studies have been carried out in the central area of ​​the province of Buenos Aires, Argentina. Benito Juárez's party constitutes one of the cases in which it has been systematically investigated for 5 years. I thighlights some peculiarities regarding the processes of enhancement and asset activation that put on the stage different, but articulated, management and participation modalities: state, alternative and community. Objective Within this framework, it is proposed to identify and analyze the discursivities that are constructed, from the native state perspective, during the act of patrimonialization of the founding stay of the party: «El Sol Argentino». Method A qualitative methodology based on participant observation during the event and analysis of public political discourses was used. Results It was possible to identify that the values ​​putting to play by the management to legitimize said cultural asset as local heritage are those referring to its materiality, especially its architectural conditions and not those related to a common history that enables new logics of meaning, use and appropriation of good. Conclusions We consider that the main challenge is to promote patrimonial practices that enable other forms of non-hegemonic reflection, of a more collective and community type.